Streamlining Non-Tariff Measures : A Toolkit for Policy Makers - Cadot, Olivier (Washington, DC: World Bank, 2012)
This volume is organized as follows. Chapter one discusses the newly revamped non-tariff measure (NTM) classification system, the data collection effort so far, and the key characteristics of the data. It also highlights the private-sector view that NTMs should support domestic firms' competitiveness across countries. Chapter two describes the analytics of an NTM review, step by step through the key questions, for example, is there a market failure, which market is affected, what are the costs of regulatory action vs. the risks of deregulation, and explains how to answer these questions and how to go about quantification when it is possible. Chapter three focuses on the institutional setup and key principles required to successfully pursue the streamlining of regulations. Since the mid-1990s, developed countries have introduced new regulatory approaches aimed at improving the quality of the decision-making process by enhancing both the analytical framework used by policy makers and the participation of interested parties in the regulatory process. Finally, chapters four and five provide practical examples of streamlining NTMs. Chapter four overviews selected experiences with tackling the trade regulatory agenda at both country and regional levels. Chapter five presents case studies on streamlining NTMs, including technical regulation and prohibition, particularly illustrating the analytics that may support the review process. Finally, NTM reviews should be seen as part of national competitiveness agendas rather than as concessions to trading partners. When NTMs are perceived by the domestic private sector as hampering access to key inputs, business regulatory reviews should naturally lead to NTM reviews. Joint use of the triangle of products will facilitate the adoption by governments of coherent national competitiveness strategies centered on the reduction of trade costs.